404 ALX148, a CD47 blocker, in combination with standard chemotherapy and antibody regimens in patients with gastric/gastroesophageal junction (GC) cancer and head and neck squamous cell carcinoma (HNSCC). (10th December 2020) - Lee, Keun-Wook; Chung, Hyun; Kim, Won Seog; Chow, Laura; Lakhani, Nehal; Messersmith, Wells; Bang, Yung-Jue; LoRusso, Patricia; Fanning, Philip; Squifflet, Pierre; Jin, Feng; Forgie, Alison; et al.
Abstract : Background: CD47 is a myeloid checkpoint up-regulated by tumors to evade the anticancer immune response. ALX148 is a high affinity CD47-blocking fusion protein with an inactive Fc region designed to safely enhance anticancer therapeutics. 1 2 ALX148 in combination with standard chemotherapy and antibody regimens was evaluated in patients (pts) with advanced HER2-positive GC or HNSCC. Methods: Pts with previously treated advanced HER2-positive GC or untreated advanced HNSCC received ALX148 (A) 10 mg/kg QW or 15 mg/kg QW in combination with trastuzumab (T) + ramucirumab (ram) + paclitaxel (pac) as 2nd or later-line treatment or pembrolizumab (P) + 5FU + platinum (cisplatin or carboplatin) as 1st line therapy, respectively. The primary endpoint was dose limiting toxicity (DLT). Tumor response, pharmacokinetic (PK), and pharmacodynamic (PD) markers were assessed in all pts. Preliminary data from enrolling cohorts, and follow-up data from pts with GC administered A+T, and with HNSCC administered A+P are also reported as of 30June2020. Results: Fifty-five pts enrolled into this portion of the study. Twelve patients with ≥2L GC received A+T+ram+pac and were evaluated for safety. No DLTs, were reported, and the ALX148 maximum administered dose was 15 mg/kg QW. Out of the 9 pts who experienced any adverse event, 7 pts reported treatment-related adverse events (TRAE). The most common TRAEs were low grade diarrhea, fatigue, pruritus and rash (each n=2, 17%). Nine of the 12 patients were response-evaluable and reported a 66% ORR with 6PR and 3SD (including one ongoing near PR, ↓29.6%). Three patients with 1L HNSCC were administered A+P+5FU+platinum. No DLTs were reported and accrual to 15 mg/kg QW continues. Three pts experienced any AE, none were treatment-related. Of 3 evaluable patients with HNSCC, 2PR and 1SD were reported. Initial ALX148 combination PK and CD47 target occupancy are similar to that of single agent administration. Response duration and survival follow-up of 19 pts with HER2-positive GC administered A+T (2nd or later-line; 21% ORR) and of 10 pts with checkpoint inhibitor naïve HNSCC administered A+P (2nd or later-line; 40% ORR) will be reported. Results of all cohorts will be updated at time of presentation. Conclusions: Initial data suggests the myeloid checkpoint inhibitor, ALX148, is well tolerated in combination with the above anticancer antibodies, T-cell checkpoint inhibitor, and cytotoxic chemotherapy regimens with early anticancer signals in GC and HNSCC that compare favorably with historic controls. No MTD has been reached in any combination to date and accrual to chemotherapy combination regimens is ongoing. Trial Registration: ClinicalTrials. gov identifier NCT03013218 Ethics Approval: The study was approved by all participating institutions' Ethics and/or Review Boards References: Kauder S, Kuo T, Harrabi O, Chen A, Sangalang E, et al. ALX148 blocks CD47 and enhances innate and adaptive antitumor immunity with a favorable safety profile. PLoS ONE 2018;13(8). Chow L, Gainor J, Lakhani N, et al. A phase I study of ALX148, a CD47 blocker, in combination with standard anticancer antibodies and chemotherapy regimens in patients with advanced malignancy. Journal of Clinical Oncology 2020;38 :15_suppl, 3056–3056.